2010
DOI: 10.1128/aem.02230-09
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Low-Energy Pulsed Ultrasonic Stimulation on Cell Surface Protein Antigen C through Heat Shock Proteins GroEL and DnaK inStreptococcus mutans

Abstract: This study concerns the use of low-energy pulsed ultrasound as nondestructive photodynamic antimicrobial therapy for controlling dental plaque. We examined the antibacterial and bactericidal effects of low-energy pulsed ultrasound on mutans streptococci and its inhibitory effects on bacterial cell adhesion of Streptococcus mutans. The results indicated weak antibacterial and bactericidal effects. However, ultrasonic stimulation for less than 20 min markedly decreased bacterial cell adhesion. To analyze the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…This result reinforces that 30°C is the optimum growth temperature for C. violaceum, in accordance with a review by Hungria et al (2004). In addition, it was previously demonstrated that, in Streptococcus mutans, the expression of proteins related to bacterial cell adhesion was dependent upon the heat shock proteins DnaK and GroEL, suggesting that these chaperones are involved in other cellular processes besides stress response (Ishibashi et al, 2010). This is consistent with the results shown in this work, as heat shock protein chaperones were expressed under all tested conditions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result reinforces that 30°C is the optimum growth temperature for C. violaceum, in accordance with a review by Hungria et al (2004). In addition, it was previously demonstrated that, in Streptococcus mutans, the expression of proteins related to bacterial cell adhesion was dependent upon the heat shock proteins DnaK and GroEL, suggesting that these chaperones are involved in other cellular processes besides stress response (Ishibashi et al, 2010). This is consistent with the results shown in this work, as heat shock protein chaperones were expressed under all tested conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Many of the stress responses overlap with one another in bacteria (Ishibashi et al, 2010) and adaptive reactions involve general changes in metabolism as well as in gene transcript levels (Jozefczuk et al, 2010;Gomes et al, 2012). The expression of heat shock genes in Gram-negative proteobacteria is positively modulated by the transcriptional regulator RpoH, the σ 32 subunit of RNA polymerase, which induces the expression of proteins involved in the response to heat and cold stress (Yura et al, 1993;El-Samad et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since many years ago, the S. mutans has been identified as the main microorganism responsible for initiating the colonization of the oral cavity, and it is capable to generate an acidic ambience favorable for the degradation of tooth mineral and protein material [18]. The diversity in its biological activity has been investigated in numerous studies with high concentrations of entire polyphenols present in EP, especially certain types of polyphenols as flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…S. mutans has been identified as the major bacteria responsible for initiating colonization of the oral cavity, and it is capable of generating an acidic environment that results in decalcification of the tooth [26]. Dental plaque control improved with the use of antiseptics, such as chlorhexidine and its derivatives, which affect oral bacteria and their attachment [27].…”
Section: Discussionmentioning
confidence: 99%